Seni Berbahasa di Era Emoji: Adaptasi Komunikasi Modern dalam Perspektif Psikolinguistik pada Mahasiswa Pengguna Media Sosial - Asmi, Nur; Sarmila, Sarmila; Pirda, Pirda Jubaeda Putri; Candra Dewi, Anita (AIJER: Algazali International Journal Of Educational Research, 2025)
This study examines the art of language in the emoji era as a modern communication adaptation from a psycholinguistic perspective. The research focuses on the semantic shift phenomenon in emoji usage among university students, particularly analyzing the crying emoji (????) which is now interpreted as laughing, and the sweet smile emoji (????) which now connotes negative emotions. Using a qualitative descriptive approach with data collected through interviews, observations, and online discourse analysis from 10 university students aged 18-24, this research reveals significant findings in language adaptation. Results show that 87% of respondents interpret the crying emoji as an expression of laughter rather than sadness, while 73% perceive the sweet smile emoji as passive-aggressive or concealing negative emotions. This semantic inversion represents a psycholinguistic phenomenon where the visual representation of emotions is reinterpreted through collective digital socialization processes. The findings contribute to understanding modern communication adaptations and have implications for intergenerational communication, digital literacy curriculum development, and psycholinguistic theory on non-verbal digital communication.